Noncanonical connections between the subiculum and hippocampal CA1. Issue 17 (6th May 2016) - Xu, Xiangmin; Sun, Yanjun; Holmes, Todd C.; López, Alberto J.
Abstract : The hippocampal formation is traditionally viewed as having a feedforward, unidirectional circuit organization that promotes propagation of excitatory processes. While the substantial forward projection from hippocampal CA1 to the subiculum has been very well established, accumulating evidence supports the existence of a significant backprojection pathway comprised of both excitatory and inhibitory elements from the subiculum to CA1. Based on these recently updated anatomical connections, such a backprojection could serve to modulate information processing in hippocampal CA1. Here we review the published anatomical and physiological studies on the subiculum to CA1 backprojection, and present recent conclusive anatomical evidence for the presence of noncanonical subicular projections to CA1. New insights into this understudied pathway will improve our understanding of reciprocal CA1–subicular connections and guide future studies on how the subiculum interacts with CA1 to regulate hippocampal circuit activity and learning and memory behaviors. J. Comp. Neurol. 524:3666–3673, 2016. © 2016 The Authors The Journal of Comparative Neurology Published by Wiley Periodicals, Inc. Abstract : In this article, we revisit the published studies on non‐canonical connections from the subiculum to CA1, and review recent conclusive evidence for the presence of excitatory and inhibitory subicular projections to CA1. New insights into this under‐studied pathway will improve our understanding of reciprocal CA1‐subicular connections and guide future studies.